[Section, Doman Moon Chapel] (1967)
A reproduction copy of the section drawing for Mark Mills' Doman Moon Chapel for the Liturgical Arts Society. This image is reproduced from an original drawing that is located in Flat File 213 Folder 6, which is where the description came from.